SELECTION OF COMPENSATION WIND FARM EQUIPMENT CONNECTED TO THE NETWORK 110 KV - Pijarski, Paweł; Gryniewicz-Jaworska, Michalina (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
Wind energy in Poland began to develop in the early 90s of the twentieth century, but its dynamic growth can be observed in subsequent years. At the end of 2014, the total installed capacity in wind farms in Poland amounted to 3 800 MW and continues to grow. The construction and installation of wind farms with high power brings with it a number of problems related to the compensation of the 110 kV cable lines of considerable length and the right type of compensation equipment. The article describes issues related to regulation of reactive power in wind farms and an analysis of individual compensation equipment used in wind energy.